Peran Absensi Online terhadap Disiplin Kerja pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Karawang - Rangga Maulana Jayadirja; Wenni Marlini (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Civil Servants (PNS), as part of the State Civil Apparatus (ASN), play a crucial role in ensuring efficient, transparent, and professional public services. One of the key indicators in assessing civil servant performance is work discipline. Work discipline includes punctuality, attendance, and responsibility for assigned tasks. To improve discipline, the Agency for Personnel and Human Resource Development (BKPSDM) of Karawang Regency has implemented an online-based Employee Attendance Information Sistem (SIAP). This sistem is designed to facilitate real-time monitoring of employee attendance, which in turn can enhance accountability and transparency. However, despite the implementation of this sistem, several problems remain, such as high rates of absenteeism, tardiness, and the potential for attendance data manipulation, all of which may undermine the sistem’s effectiveness. These issues indicate that the application of digital technology has not fully resolved the challenges of work discipline in government institutions.This study aims to analyze the effect of online attendance implementation on the work discipline of employees in Karawang Regency. The research employed a quantitative approach using a survey of 68 civil servants, with data analyzed through t-tests, coefficient of determination, and Pearson Product Moment correlation. The results show a very strong positive relationship between online attendance and work discipline, with a correlation value of 0.959 and a contribution of 92%. These findings demonstrate that online attendance implementation significantly improves employee discipline. Based on these results, it is recommended that the sistem be further enhanced through increased transparency, strengthened supervision mechanisms, and continuous discipline development. With these measures, the online attendance sistem can function more optimally in supporting civil servant discipline in Karawang Regency.